The effect of various heat-treatment methods on colostrum quality, health and performance of dairy calves - Hesami, Saeid; Shahraki, Amir-Davar Foroozandeh; Zakian, Amir; Ghalamkari, Gholamreza (Acta Scientiarum. Animal Sciences, 2020)
To investigate the effect of feeding heat-treated colostrum at different duration on the health and performance, 48 Holstein calves were enrolled randomly into four treatment groups before first feeding and consumed untreated colostrum (H0, n = 12), heat-treated colostrum at 60ºC for 30 min. (H30, n = 12), heat-treated colostrum at 60ºC for 60 min. (H60, n = 12) and heat-treated colostrum at 60ºC for 90 min. (H90, n = 12). Blood samples were collected for analyses of IgG and protein profile at 0, 6, and 24h of age. The colostrum sample from treated and untreated batches and feces sample from each calf also were taken. The results showed heat-treatment of colostrum at 60ºC for 60 (p = 0.03) and 90 min. (p = 0.01) reduced total bacterial count, while colostral IgG concentration maintained up to 60 min. Serum total protein (p = 0.02), IgG concentrations (p = 0.03), and apparent efficiency of IgG absorption (p = 0.02) were significantly greater at 6 and 24h in calves that were fed heat-treated colostrum (H90) compared to calves fed unheated colostrum (H0). General health status of calves that were received heat-treated colostrum was better and the prevalence of diarrhea-induced pathogens was lower than calves were fed unheated colostrum. In conclusion, the consumption of heat-treated colostrum had a positive effect on health, growth characteristics, and performance of calves during the suckling period.